Trapping-a major tactic of BIPM strategy of palm weevils - S. P., Singh; Ponniah, Rethinam (International Coconut Community Journal, 2005)
Several species of curculionid weevils such as Amerrhinus ynca Sahlberg, Cholus annulatus Linnaeus, C. martiniquensis Marshall, C. zonatus (Swederus), Diocalandra frumenti (Fabricius), Dynamis borassi Fabricius, Homalinotus coriaceus Gyllenhal, Metamasius hemipterus Linnaeus, Paramasius distortus (Gemminger & Horold), Rhabdoscelus obscurus (Boisduval), Rhinostomus barbirostris (Fabricius), R. afzelii (Gyllenhal), Rhynchophorus bilineatus (Montrouzier), R. cruentatus Fabricius, R. ferrugineus (Olivier), R. palmarum (Linnaeus) and R. phoenicis (Fabricius) are associated with palms. Some of these have become a major constraint in the successful cultivation of coconut palm (Cocos nucifera L.), date palm (Phoenix dactylifera L.) and oil palm (Elaeis guineensis L.). R. ferrugineus is distributed in over 33 countries and attacks more than two dozen palm species. In the recent past, it has spread to Middle Eastern countries, Mediterranean region of Africa and southern Europe (Spain) causing tremendous economic losses. The yield of date palm has decreased from 10 to 0.7 tons/ha. Coconut palms in India are infested upto 6.9 per cent in Kerala and 11.65 per cent in Tamil Nadu. R. palmarum is a major pest of oil and coconut palms in the tropical Americas and, vectors the nematode, Bursaphelenchus cocophilus (Cobb) Baujard which causes red ring disease (RRD). Palm losses due to RRD are commonly between 0.1 to 15% which amounts to tens of millions dollars. The status of other species is briefed. The grubs of weevils that develop in the stems, bud, rachis of leaves and inflorescence of cultivated, ornamental or wild palms cause direct damage. Because of the cryptic habitat of the grubs, which act as tissue borer, the management becomes difficult.